Kinetic investigation of the energy storage process in graphene fiber supercapacitors: Unraveling mechanisms, fabrications, property manipulation, and wearable applications - Juan Zhang; Wenwen Liu; Minzhi Du; Qingli Xu; Minren Hung; Ruifang Xiang; Meng Liao; Xinhou Wang; Bingjie Wang; Aiping Yu; Kun Zhang (Carbon Energy)
Abstract Graphene fiber supercapacitors (GFSCs) have garnered significant attention due to their exceptional features, including high power density, rapid charge/discharge rates, prolonged cycling durability, and versatile weaving capabilities. Nevertheless, inherent challenges in graphene fibers (GFs), particularly the restricted ion‐accessible specific surface area (SSA) and sluggish ion transport kinetics, hinder the achievement of optimal capacitance and rate performance. Despite existing reviews on GFSCs, a notable gap exists in thoroughly exploring the kinetics governing the energy storage process in GFSCs. This review aims to address this gap by thoroughly analyzing the energy storage mechanism, fabrication methodologies, property manipulation, and wearable applications of GFSCs. Through theoretical analysis of the energy storage process, specific parameters in advanced GF fabrication methodologies are carefully summarized, which can be used to modulate nano/micro‐structures, thereby enhancing energy storage kinetics. In particular, enhanced ion storage is realized by creating more ion‐accessible SSA and introducing extra‐capacitive components, while accelerated ion transport is achieved by shortening the transport channel length and improving the accessibility of electrolyte ions. Building on the established structure–property relationship, several critical strategies for constructing optimal surface and structure profiles of GF electrodes are summarized. Capitalizing on the exceptional flexibility and wearability of GFSCs, the review further underscores their potential as foundational elements for constructing multifunctional e‐textiles using conventional textile technologies. In conclusion, this review provides insights into current challenges and suggests potential research directions for GFSCs.